The magnitude of postpartum depression among mothers in Africa: a literature review - Atuhaire, Catherine; Laura, Brennaman; Samuel, Nambile Cumber; Rukundo, Godfrey Zari; Nambozi, Grace (Pan African Medical Journal, 2020)
Introduction: postpartum depression (PPD) continues to become one of the major maternal health challenges across the globe but there is a paucity of recent data on its magnitude in Africa. This study was motivated by the need to update the current magnitude of PPD in Africa based on various assessment tools. Methods: a total of 21 articles met the study criteria. Fifteen articles used the EPDS and six used other assessment tools. Postpartum depression among studies that used EPDS tool ranged from 6.9% in Morocco to 43% in Uganda and 6.1% in Uganda to 44% in Burkina Faso among studies that used other depression assessment tools. Sensitivity and specificity results of the EPDS ranged from 75%-100% and 87%-98% respectively. Results: a total of 21 articles met the study criteria. Fifteen articles used the EPDS and six used other assessment tools. Postpartum depression among studies that used EPDS tool ranged from 6.9% in Morocco to 43% in Uganda and 6.1% in Uganda to 44% in Burkina Faso among studies that used other depression assessment tools. Sensitivity and specificity results of the EPDS ranged from 75%-100% and 87%-98% respectively. Conclusion: despite the limited dearth of literature, the magnitude of PPD in Africa remains high which suggests that PPD is still a neglected illness and calls for immediate interventions. EPDS is an effective tool with high sensitivity and specify in varying study contexts.